(untitled) (The Journal of Medicine, Humanity and Media, 2025)
As digital technologies, such as artificial intelligence (AI), become increasingly common in daily life, their impact on sociotechnical inequality grows more significant. On July 6, 2025, the second session of the 8th International Conference on "Medicine, Humanity, and Media" (MHM 2025) was held under the theme "Sociotechnical Inequality, Cultural Metaphors, and the Plight of Marginalized Groups in Health Communication." This session was moderated and reviewed by JIANG Crystal Li, Associate Professor at the Department of Media and Communication, City University of Hong Kong, and HE Qijun, Associate Professor at the School of Journalism and Communication, Shanghai University. During the session, five scholars presented their latest research covering diverse topics, including depression-related memes, the digital divide, intercultural health communication narratives, the experiences of senior Chinese immigrants, and social inequalities related to the adoption of AI. The symposium gathered health communication researchers from various countries and highlighted the importance of effective health communication in addressing social inequalities in the digital era.